Training a champion - Bidrman, J. (Swimming Technique, 2000)
Penny Heyns had one of the most remarkable swimming seasons ever last year, breaking world records in the 50, 100 and 200 meter breaststrokes on 11 different occasions! Her coach, Jan Bidrman, shares how he trained Penny from May 1998 through her memorable summer of 1999. see also: http://www.gsv1.de/heyns.htm